2009
DOI: 10.1371/journal.pone.0005871
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Host-Mediated Repair Mechanisms after Human CNS-Stem Cell Transplantation for Spinal Cord Injury: Correlation of Engraftment with Recovery

Abstract: BackgroundHuman central nervous system-stem cells grown as neurospheres (hCNS-SCns) self-renew, are multipotent, and have potential therapeutic applications following trauma to the spinal cord. We have previously shown locomotor recovery in immunodeficient mice that received a moderate contusion spinal cord injury (SCI) and hCNS-SCns transplantation 9 days post-injury (dpi). Engrafted hCNS-SCns exhibited terminal differentiation to myelinating oligodendrocytes and synapse-forming neurons. Further, selective ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 107 publications
(136 reference statements)
10
135
2
1
Order By: Relevance
“…3D-3F), even though endogenous or transplanted NSCs in the injured spinal cord have been reported by others to differentiate preferentially into the glial lineage [42,43]. Recent studies have indicated that neurons derived from transplanted human NSCs can integrate into the injured spinal cord and form synaptic connections with host neurons [33,34]. We therefore took advantage of the tendency of our hiPS-lt-NES cells to differentiate into neurons and tried to apply these cells to reconstruction of the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3D-3F), even though endogenous or transplanted NSCs in the injured spinal cord have been reported by others to differentiate preferentially into the glial lineage [42,43]. Recent studies have indicated that neurons derived from transplanted human NSCs can integrate into the injured spinal cord and form synaptic connections with host neurons [33,34]. We therefore took advantage of the tendency of our hiPS-lt-NES cells to differentiate into neurons and tried to apply these cells to reconstruction of the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the sources and methods of induction of NSCs are critical for differentiation and tumor formation [33,53]. Neurosphere cultures are heterogeneous and sensitive to variations in methodological procedures [12], whereas monolayer cell cultures give rise to more homogeneous population [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment mechanism study indicated that neurons derived from transplanted stem cells integrated into the host neuronal circuitry and mediated functional recovery [19,67] . On the other hand, the functional recovery after NSC transplantation into spinal cord injury models was proportional to the number of transplanted stem cell-derived oligodendrocytes and the amount of regenerated myelin [68] .…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…Кли-нические испытания проводились на основе предклинических исследований, показавших, что стволовые клетки, выделенные из фе-тального мозга человека, могут дифференци-роваться в миелин-продуцирующие олиго-дендроциты и нейроны, формирующие новые синапсы, что приводит к функциональному восстановлению на моделях ПСМТ грызунов [54][55][56][57][58]. Клиническое исследование было на-чато в марте 2011 года и в настоящее время завершено.…”
Section: обонятельные клетки слизистой оболочки носовой полости (Oecsunclassified